Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By using a single particle of a lithium transition metal composite oxide containing Ni and Mn and forming a boron compound modification layer on its surface, the problem of difficulty in balancing high capacity and high durability in the existing technology is solved, and a secondary non-aqueous electrolyte is achieved. Efficient battery performance.
Patent Information
- Application Number
- CN202380047076.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-16
- Publication Date
- 2025-01-24
AI Technical Summary
As the positive electrode active substance of a nonaqueous electrolyte secondary battery, the existing lithium transition metal composite oxide is difficult to take into account both high capacity and high durability.
The lithium transition metal composite oxide single particles containing more than 70 Moore % of Ni and MN are used as positive active substances. The average particle size of the single particles is 0.65 μm ~ 4 μm, and the surface modifier containing a boron compound is formed on its surface.
The high capacity and high durability of the secondary battery of non -hydrolysis quality, at the same time inhibit the production of gas and improve the charge and discharge efficiency.
Smart Images

Figure CN119366001A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art
[0002] As a positive electrode active material of a lithium ion secondary battery of a non-aqueous electrolyte secondary battery, a lithium transition metal composite oxide is used. In recent years, in order to improve durability, research has been conducted on the single particle formation of lithium transition metal composite oxides. For example, Patent Document 1 discloses a single particle having an average particle size of 2 μm to 20 μm and a BET specific surface area of 0.15 m 2 / g~1.9m 2 / g, single particles of NCM-based lithium transition metal composite oxide (Ni content of 0.3≤Ni≤0.6) to which boron is added. In addition, Patent Document 2 discloses a single particle having an average particle size of 3 μm to 8 μm and a crystallite size of A single particle of an NCM-based lithium transition metal composite oxide (Ni content is 0.3≤Ni≤0.6).
[0003] Prior Art Literature
[0004] Patent Document 1: Japanese Patent Application No. 2018-532236
[0005] Patent Document 2: Japanese Patent No. 6850949 Summary of the invention
[0006] The present inventors have conducted in-depth research and found that even single-particle lithium transition metal composite oxides have poor durability. In addition, the present inventors have further repeatedly studied and found that in single particles, battery capacity and durability cannot sometimes be taken into account. Patent documents 1 and 2 do not take into account the simultaneous realization of high capacity and high durability, and there is still room for improvement.
[0007] An object of the present disclosure is to provide a positive electrode active material for a non-aqueous electrolyte secondary battery capable of improving the capacity and durability of the non-aqueous electrolyte secondary battery.
[0008] A positive electrode active material for a non-aqueous electrolyte secondary battery according to a technical solution of the present disclosure is characterized in that it comprises a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide contains 70 mol % or more of Ni and Mn relative to the total molar amount of metal elements other than Li, and the lithium transition metal composite oxide is composed of single particles, the average particle size of the single particles is 0.65 μm to 4 μm, and the crystallite size of the single particles is
[0009] A nonaqueous electrolyte secondary battery according to one aspect of the present disclosure includes a positive electrode, a negative electrode, and a nonaqueous electrolyte, wherein the positive electrode includes the positive electrode active material.
[0010] According to a positive electrode active material for a nonaqueous electrolyte secondary battery according to one aspect of the present disclosure, a nonaqueous electrolyte secondary battery having a high capacity and improved durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is an axial cross-sectional view of a nonaqueous electrolyte secondary battery according to an example of the embodiment.
[0012] Figure 2 It is a schematic cross-sectional view of a test cell prepared in Examples and Comparative Examples.
[0013] Figure 3 These are SEM images of the positive electrode active material of Example C1 before and after pulverization.
[0014] Figure 4 These are SEM images of the positive electrode active material of Example C2 before and after pulverization.
[0015] Figure 5 These are SEM images of the positive electrode active material of Example C3 before and after pulverization.
[0016] Figure 6 These are SEM images of the positive electrode active material of Comparative Example C4 before and after pulverization.
[0017] Figure 7 These are SEM images of the positive electrode active material of Comparative Example C5 before and after pulverization. DETAILED DESCRIPTION
[0018] In recent years, along with the popularization of nonaqueous electrolyte secondary battery in vehicle-mounted use and storage power use, nonaqueous electrolyte secondary battery with high capacity and excellent durability is more and more needed.In addition, also expect the low cost of nonaqueous electrolyte secondary battery, as positive electrode active material, preferably with relatively cheap Ni and Mn as main component material.For the purpose of improving durability, the single particle of lithium transition metal composite oxide as positive electrode active material has been studied, but there are still many unclear points about the characteristics of single particle.
[0019] The present inventors have conducted intensive studies to solve the above problems and have found that both high capacity and high durability can be achieved by setting single particles of a lithium transition metal composite oxide containing Ni and Mn as main components to have a predetermined average particle diameter and crystallite size.
[0020] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery of the present disclosure is described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is housed in a cylindrical outer casing is exemplified, but the electrode body is not limited to a wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one sheet each through a separator. The outer casing is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc. In addition, the outer casing may also be a bag-type composed of a laminated sheet comprising a metal layer and a resin layer. In addition, in this specification, the description of "value (A) to value (B)" means above value (A) and below value (B).
[0021] Figure 1 FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 according to an example of an embodiment. Figure 1 In the secondary battery 10 shown, an electrode body 14 and a non-aqueous electrolyte (not shown) are accommodated in an outer body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. In addition, for the sake of convenience in the following description, the sealing body 16 side is referred to as "upper" and the bottom side of the outer body 15 is referred to as "lower".
[0022] The interior of the secondary battery 10 is sealed by blocking the upper end of the outer body 15 with the sealing body 16. Insulating plates 17 and 18 are respectively provided above and below the electrode body 14. The positive lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the lower surface of the filter 22 which is the bottom plate of the sealing body 16. In the secondary battery 10, the cover 26 which is the top plate of the sealing body 16 electrically connected to the filter 22 serves as the positive terminal. On the other hand, the negative lead 20 extends to the bottom side of the outer body 15 through the through hole of the insulating plate 18 and is welded to the bottom inner surface of the outer body 15. In the secondary battery 10, the outer body 15 serves as the negative terminal. In addition, when the negative lead 20 is provided at the outer end of the roll, the negative lead 20 extends to the bottom side of the outer body 15 through the outside of the insulating plate 18 and is welded to the bottom inner surface of the outer body 15.
[0023] The outer body 15 is, for example, a metal outer can with a bottomed cylindrical shape. A gasket 27 is provided between the outer body 15 and the sealing body 16 to ensure the airtightness inside the secondary battery 10. The outer body 15 has, for example, a groove 21 formed by punching the side surface from the outside to support the sealing body 16. The groove 21 is preferably formed in an annular shape along the circumferential direction of the outer body 15, and the sealing body 16 is supported on its upper surface via the gasket 27.
[0024] The sealing body 16 has a filter 22, a lower valve body 23, an insulating component 24, an upper valve body 25 and a cover 26 stacked in sequence from the electrode body 14 side. The components constituting the sealing body 16 have, for example, a disc shape or a ring shape, and the components except the insulating component 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, and an insulating component 24 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat, for example, the lower valve body 23 breaks, whereby the upper valve body 25 expands toward the cover 26 side and leaves the lower valve body 23, thereby cutting off the electrical connection between the two. When the internal pressure rises further, the upper valve body 25 breaks, and the gas is discharged from the opening 26a of the cover 26.
[0025] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the electrode body 14 , particularly the positive electrode 11 , will be described in detail.
[0026] [positive electrode]
[0027] The positive electrode 11 has a positive electrode collector and a positive electrode mixture layer formed on the surface of the positive electrode collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode collector. The positive electrode collector can use a foil of a metal such as aluminum or aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film having the metal disposed on the surface, and the like. The positive electrode mixture layer contains, for example, a positive electrode active material, a conductive agent, a binder, and the like. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm on one side of the positive electrode collector. The positive electrode 11 is produced, for example, by coating a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder on the surface of the positive electrode collector, drying the coating, and then rolling the coating to form positive electrode mixture layers on both sides of the positive electrode collector.
[0028] As the conductive agent contained in the positive electrode mixture layer, carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon particles can be exemplified. These can be used alone or in combination of two or more. Relative to 100 parts by mass of the positive electrode active material, the content of the conductive agent is, for example, 0.1% by mass to 5.0% by mass.
[0029] As the binder contained in the positive electrode mixture layer, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. These resins can be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc. Relative to 100 parts by mass of the positive electrode active material, the content of the binder is, for example, 0.1% by mass to 5.0% by mass.
[0030] The positive electrode active material contained in the positive electrode mixture layer includes a lithium transition metal composite oxide. The lithium transition metal composite oxide is composed of single particles. In addition to single particles, the positive electrode active material may also contain secondary particles formed by agglomeration of single particles. As a result, the charging density of the positive electrode active material in the positive electrode mixture layer is increased, so that the capacity of the secondary battery 10 can be increased. The secondary particles formed by the agglomeration of single particles are formed by the agglomeration of, for example, 2 to 1000 single particles. In addition, general primary particles that are not single particles, and secondary particles formed by the agglomeration of the primary particles may also be included. In addition, in addition to the lithium transition metal composite oxide, the positive electrode active material may also contain LiF, Li2S, etc.
[0031] The proportion of single particles in the positive electrode active material is preferably 10% or more, more preferably 80% or more, particularly preferably 90% or more, and can be substantially 100%. In addition, the lithium transition metal composite oxide may contain secondary particles formed by agglomeration of more than 100 primary particles.
[0032] The average particle size of a single particle is 0.65 μm to 4 μm. In this specification, the average particle size refers to the median particle size (D50) based on volume. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the positive electrode active material can be measured using a laser diffraction particle size distribution measuring device (for example, MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as the dispersion medium. If the particle size of a single particle is too large, the battery capacity decreases, or the charge and discharge efficiency deteriorates. If the particle size of a single particle is too small, secondary aggregation will occur, which becomes the main cause of battery deterioration.
[0033] The BET specific surface area of a single particle is, for example, 0.5 m 2 / g~4m 2 / g. Since there are voids in the particles of secondary particles, the specific surface area is relatively large even if the particle size is large. On the other hand, since there are no voids in the particles of single particles, the larger the particle size, the smaller the BET specific surface area. The particle shapes of secondary particles and single particles change in various ways depending on the production conditions, so the BET specific surface area changes. The determination of BET specific surface area can be measured using TriStarII3020 (manufactured by Shimadzu Corporation) under the following conditions.
[0034] Measurement score: 11 points (P / P0: 0.05~0.3)
[0035] Thermal Free Space: Measurements
[0036] Balance interval: 5s
[0037] Adsorption analysis: N2
[0038] Analysis tank temperature: 77.3K (liquid nitrogen temperature)
[0039] Cold Free Space: Measurements
[0040] Low pressure finish: No
[0041] Analysis method: BET multi-point method
[0042] The BET specific surface area of the lithium transition metal composite oxide is defined as A (m 2 / g), when the average particle size of the lithium transition metal composite oxide is set to B (μm), the product AB of A and B preferably satisfies 1.5≤AB≤6. As a result, the battery capacity and durability of the secondary battery 10 are significantly improved. Secondary particles formed by the agglomeration of single particles with small particle sizes sometimes lead to reduced charge and discharge cycle characteristics due to the rupture of crystal boundaries (grain boundaries). Single particles with large particle sizes may have reduced battery capacity. In addition, if the BET specific surface area of a single particle is small, the contact area with the non-aqueous electrolyte is small, and there is a situation where the battery capacity is reduced or the load characteristics are deteriorated. If the BET specific surface area of a single particle is large, many side reactions such as gas generation will occur at the positive electrode, and there is a situation where the charge and discharge cycle characteristics are reduced. Therefore, by making the product of the average particle size (D50) and the BET specific surface area within the above range, a secondary battery 10 with high capacity, high durability and suppressed gas generation can be obtained.
[0043] The crystallite size of a single particle is By making the single particle have the above-mentioned average particle size and crystallite size, a secondary battery 10 with high capacity and improved durability can be obtained. Here, the crystallite size is calculated by the Scherrer formula represented by the following formula based on the half-value width of the diffraction peak of the (104) plane of the X-ray diffraction pattern of X-ray diffraction. In the following formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-value width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In the present embodiment, K is 0.9.
[0044] s=Kλ / Bcosθ
[0045] The X-ray diffraction pattern was obtained by powder X-ray diffraction under the following conditions using a powder X-ray diffractometer (manufactured by Rigaku Corporation, trade name “RINT-TTR”, source Cu—Kα).
[0046] Measuring range: 15-120°
[0047] Scanning speed: 4° / min
[0048] Analysis range: 30~120°
[0049] Background: B-spline curves
[0050] Contour function: segmentation quasi-Voigt function
[0051] Binding condition: Li(3a)+Ni(3a)=1
[0052] Ni(3a)+Ni(3b)=α (α is the Ni content ratio of each)
[0053] ICSD No.:98-009-4814
[0054] The lithium transition metal composite oxide contains 70 mol % or more of Ni and Mn relative to the total molar amount of metal elements other than Li. Thus, a relatively cheap and high-capacity lithium transition metal composite oxide can be obtained. In addition, the lithium transition metal composite oxide can also be composed of only Ni and Mn.
[0055] Among the metal elements other than Li constituting the lithium transition metal composite oxide, Ni is preferably contained at most. The content of Ni in the lithium transition metal composite oxide is preferably 50 mol% or more, more preferably 70 mol% or more, relative to the total molar amount of the metal elements other than Li. The upper limit of the Ni content can be 95 mol%, preferably 90 mol%.
[0056] Among the metal elements other than Li constituting the lithium transition metal composite oxide, Mn is preferably contained in the second largest amount after Ni. Mn can stabilize the crystal structure of the lithium transition metal composite oxide. The content of Mn in the lithium transition metal composite oxide is, for example, 5 mol% to 50 mol% relative to the total molar amount of the metal elements other than Li.
[0057] By using a single particle, a high capacity retention rate can be maintained even at a high charge potential. In particular, lithium transition metal composite oxides having a Ni content of 80% or less and a high Mn content in the composition require single particles with high potential resistance because high capacity is obtained by increasing the charge potential.
[0058] A surface modification layer containing a boron compound can be formed on the surface of a single particle. As a result, the charge and discharge efficiency is improved. It is speculated that the boron compound inhibits the decomposition of the electrolyte and promotes the exchange of Li ions between the non-aqueous electrolyte on the surface of the lithium transition metal composite oxide and the positive electrode active material. A boron compound refers to a compound containing B (boron). Boron compounds are, for example, boron oxides, boron fluorides, boron chlorides, and boron sulfides. The boron compound is preferably a boron oxide. Boron oxides include, for example, boric acid (H3BO3), boric oxide (B2O3), and lithium borate (LiBO2, LiB3O5, Li2B4O7). The boron compound present on the surface of the lithium transition metal composite oxide can be confirmed by low-acceleration SEM or TEM-EDX, etc.
[0059] The thickness of the surface modification layer is, for example, 1 nm to 100 nm. The amount of the boron compound in the surface modification layer is, for example, 0.1 mol % to 7 mol % relative to the total molar amount of metal elements other than Li in the single particle. The atomic concentration of each element can be measured by X-ray photoelectron spectroscopy (XPS).
[0060] The lithium transition metal composite oxide may further contain at least one metal element selected from Ca, Sr, W and S. These metal elements may be contained in the lithium transition metal composite oxide, but are preferably present on the surface of the lithium transition metal composite oxide. Thus, the side reaction between the lithium transition metal composite oxide and the electrolyte can be suppressed, and the degradation of the battery can be suppressed. These metal elements may be contained in the surface modification layer together with B. These metal elements in the positive electrode active material may contain, for example, 0.01 mol% to 5 mol% relative to the total amount of Ni and Mn.
[0061] Next, an example of a method for producing a positive electrode active material according to the present embodiment is described. The method for producing a positive electrode active material includes, for example, a synthesis step, a washing step, a drying step, and a pulverization step.
[0062] In the synthesis step, a metal hydroxide containing 70 mol % or more of Ni and Mn is mixed with a Li compound and calcined to obtain a lithium transition metal composite oxide.
[0063] Metal hydroxides can be obtained, for example, by stirring a solution of a metal salt containing Ni, Mn and any metal element (Fe, etc.) while dropping an alkaline solution such as sodium hydroxide to adjust the pH to alkaline (e.g., 8.5 to 12.5) to precipitate (coprecipitate). In addition, metal oxides obtained by heat-treating metal hydroxides can also be used instead of metal hydroxides. The smaller the particle size of the metal hydroxide, the easier it is for the primary particles to grow, so it is preferably less than 7 μm.
[0064] As Li compounds, for example, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be mentioned. From the viewpoint of easily adjusting the above parameters to the above-mentioned specified ranges, the mixing ratio of the metal hydroxide and the Li compound is preferably, for example, a ratio in the range of 1:0.98 to 1:1.1 in which the molar ratio of the metal element other than Li:Li is. In addition, when mixing the metal hydroxide and the Li compound, Ca compounds, Sr compounds, W compounds, etc. can be added. As Ca compounds, for example, CaO, Ca(OH)2 and CaCO3 can be mentioned. As Sr compounds, for example, SrO, Sr(OH)2 and SrCO3 can be mentioned. As W compounds, for example, WO3, Li2WO4, Li4WO5 and Li6W2O9 can be mentioned.
[0065] A mixture of metal hydroxide and Li compound, etc. is calcined, for example, in an oxygen atmosphere (gas with a flowing oxygen concentration of 80% or more). The calcination conditions may be a temperature rise rate of more than 1.0°C / minute and less than 5.5°C / minute from 450°C to 680°C, and a maximum temperature reached in the range of more than 850°C and less than 1100°C. The temperature rise rate from more than 680°C to the maximum temperature reached may be, for example, 0.1°C / minute to 3.5°C / minute. In addition, the holding time of the maximum temperature reached may be more than 1 hour and less than 30 hours. In addition, the calcination process may be a multi-stage calcination, and multiple temperature zones may be set as long as the first temperature rise rate and the second temperature rise rate are within the above-specified range. By adjusting the calcination conditions, the particle size of the single particle can be adjusted. For example, by increasing the maximum temperature reached, the particle size of the single particle can be increased.
[0066] In the cleaning step, the lithium transition metal composite oxide obtained in the synthesis step is washed with water and dehydrated to obtain a cake-like composition. The washing and dehydration can be carried out by known methods and conditions. It can be carried out within a range where lithium does not dissolve from the lithium transition metal composite oxide and deteriorate the battery characteristics. In addition, a Ca compound, an Sr compound, a W compound, an S compound, a P compound, etc. can be added to the cake-like composition.
[0067] In the drying step, the cake-like composition obtained in the washing step is dried to obtain a powdery composition. The drying step may be performed in a vacuum atmosphere. The drying conditions are, for example, 150° C. to 400° C. and 0.5 to 15 hours.
[0068] The powdery composition obtained in the drying step can be pulverized to obtain single particles. The pulverization can be performed using a jet mill or the like. The pulverization by a jet mill can be performed using, for example, PJM-80 (manufactured by Nippon Newmar NPK) under the following conditions.
[0069] Compressed air consumption: 0.5Nm 3 / minute
[0070] Supply gas pressure: 0.53MPa
[0071] Processing capacity: 2000g / hour
[0072] A boron-containing compound such as boric acid (H3BO3) can be added to the obtained single particle, and the temperature is raised to 200°C to 400°C, thereby forming a surface modification layer containing the boron compound on the surface of the single particle. The amount of the boron-containing compound added is, for example, 0.1 mol% to 7 mol% relative to the total molar amount of the metal elements other than Li in the lithium transition metal composite oxide.
[0073] [negative electrode]
[0074] The negative electrode 12 has a negative electrode collector and a negative electrode mixture layer formed on the surface of the negative electrode collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. The negative electrode collector can use a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, a thin film having the metal disposed on the surface, and the like. The negative electrode mixture layer, for example, contains a negative electrode active material, a binder, and the like. The negative electrode 12 is produced, for example, by coating a negative electrode mixture slurry containing a negative electrode active material and a binder on the surface of the negative electrode collector, drying the coating, and then rolling to form a negative electrode mixture layer on both sides of the negative electrode collector.
[0075] The negative electrode 12 may contain boron. A portion of the boron present on the surface of the positive electrode active material sometimes moves from the positive electrode 11 to the negative electrode 12. Even in the case where a metal element such as Ni is precipitated on the surface of the negative electrode, by making it coexist with B, the degradation of the battery can be suppressed. The amount of boron contained in the negative electrode is preferably 50 μg or more, more preferably 400 μg or more and 1200 μg or less per 1g of the positive electrode active material. For example, of the boron added to the positive electrode, more than 35% is precipitated to the negative electrode, and less than 55% remains in the positive electrode.
[0076] The negative electrode active material contained in the negative electrode mixture layer includes, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Preferred carbon-based active materials include natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite (MAG), and graphitized mesophase carbon microbeads (MCMB) and other artificial graphites. In addition, the negative electrode active material can use a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material can be used in combination.
[0077] As the binder contained in the negative electrode mixture layer, fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc. can be used as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer preferably also contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, SBR, CMC or its salt, PAA or its salt are preferably used in combination. In addition, the negative electrode mixture layer may contain a conductive agent.
[0078] [Diaphragm]
[0079] The separator 13 uses a porous sheet having ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are preferred. The separator 13 can be a single-layer structure or a laminated structure. In addition, a resin layer with high heat resistance such as aramid resin and a filler layer containing a filler of an inorganic compound can be provided on the surface of the separator 13.
[0080] [Non-aqueous electrolyte]
[0081] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent can use, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The non-aqueous solvent can contain a halogen substituted substance in which at least a portion of the hydrogen atoms of these solvents are substituted by halogen atoms such as fluorine. As the halogen substituted substance, fluorinated cyclic carbonates such as fluorinated ethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as methyl fluoropropionate (FMP), etc. can be cited.
[0082] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.
[0083] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl Chain ethers such as 1,2-diethylene glycol dimethyl ether, 1,2-diethylene glycol diethyl ether, 1,2-diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, ...
[0084] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic carboxylic acid lithium, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C l F 2l+1 SO2)(C m F 2m+1 SO2) {l, m is an integer greater than 0} and other imide salts. The lithium salt can be used alone or in combination. Among them, LiPF6 is preferably used from the viewpoint of ion conductivity, electrochemical stability, etc. The concentration of the lithium salt is preferably 0.8 mol to 1.8 mol per 1L of the non-aqueous solvent.
[0085] Example
[0086] Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.
[0087] [Preparation of positive electrode active material]
[0088] <Positive electrode active material A1>
[0089] LiOH and Ni with an average particle size of 6 μm obtained by coprecipitation 0.5 Mn0.5 The (OH)2 powder is mixed so that the molar ratio of Li to the total amount of Ni and Mn is 1.1:1 to obtain a mixture. Under an oxygen flow with an oxygen concentration of more than 90% (a flow rate of 0.15 to 0.2 L / min relative to the volume of 1 L of the furnace), the mixture is calcined from room temperature to 650°C for 5 hours, then calcined at 1000°C for 2 hours, and maintained for 9 hours to obtain a lithium transition metal composite oxide. The remaining lithium of the lithium transition metal composite oxide is removed by washing with water, and the composite oxide is dried to obtain secondary particles formed by agglomeration of single particles. Furthermore, the secondary particles are crushed with a jet mill to obtain the positive electrode active material A1.
[0090] <Positive electrode active materials A2 to A5>
[0091] Positive electrode active materials A2 to 5 were obtained in the same manner as positive electrode active material A1 except that the maximum peak temperature was changed as shown in Tables 1 and 3.
[0092] <Positive electrode active materials B1 to B4>
[0093] Changing the composition of the mixed hydroxide to Ni 0.6 Mn 0.4 (OH)2, and except that the maximum peak temperature was changed as shown in Tables 1 and 3, positive electrode active materials B1 to 4 were obtained in the same manner as positive electrode active material A1.
[0094] <Positive electrode active materials C1 to C5>
[0095] In the preparation of the positive electrode active material, the composition of the mixed hydroxide is changed to Ni 0.7 Mn 0.3 (OH)2, and the maximum reaching temperature was changed as shown in Tables 1 and 3. Positive electrode active materials C1 to 5 were obtained in the same manner as positive electrode active material A1. SEM images of positive electrode active materials C1 to 5 before and after pulverization are shown in Figures 3 to 7 .exist Figure 3 , 4 Before the pulverization of 6, both of them are in the shape of secondary particles formed by the aggregation of primary particles. Figure 3 and 4 After the pulverization, the shape of the single particle can be confirmed. Figure 6 After the pulverization, the shape of the single particle cannot be confirmed. Thus, even if the shapes of the secondary particles in the SEM image are roughly the same, there are cases where the particles are single particles and cases where they are not single particles. Figure 3 As shown in the figure, even if it is crushed into single particles and a part of the agglomerate remains, as long as the average particle size of the single particles is 0.65μm to 4μm and the crystallite size of the single particles is will behave as a single particle. Figure 6As shown in , the particles that are almost not broken are not single particles and do not show the effect of single particles. Figure 5 and 7 As shown in , there are also cases where the particles are in single particle form before being crushed. Figure 7 As in the examples shown, if the average particle size or crystallite size of the particles is outside the above range, the battery characteristics cannot be sufficiently improved.
[0096] <Positive electrode active materials D1 to D3>
[0097] In the preparation of the positive electrode active material, the composition of the mixed hydroxide is changed to Ni 0.75 Mn 0.25 (OH)2, and except that the maximum peak temperature was changed as shown in Tables 1 and 3, positive electrode active materials D1 to 3 were obtained in the same manner as positive electrode active material A1.
[0098] <Positive electrode active material E1>
[0099] Boric acid (H3BO3) was added to the positive electrode active material A1 and heat treated to form a surface modification layer containing a boron compound on the surface of the positive electrode active material A1, thereby obtaining a positive electrode active material E1. The amount of boric acid added was 2 mol% relative to the total molar amount of metal elements other than Li in the single particle.
[0100] <Positive electrode active materials E2 to 4>
[0101] Positive electrode active materials E2 to 4 were obtained in the same manner as positive electrode active material E1 except that the maximum peak temperature was changed as shown in Tables 2 and 4.
[0102] <Positive electrode active materials F1 to 4>
[0103] Changing the composition of the mixed hydroxide to Ni 0.6 Mn 0.4 (OH)2, and except that the maximum reaching temperature was changed as shown in Tables 2 and 4, positive electrode active materials F1 to 4 were obtained in the same manner as positive electrode active material E1.
[0104] <Positive electrode active materials G1 to G4>
[0105] In the preparation of the positive electrode active material, the composition of the mixed hydroxide is changed to Ni 0.7 Mn 0.3 (OH)2, and except that the maximum reaching temperature was changed as shown in Tables 2 and 4, positive electrode active materials G1 to 4 were obtained in the same manner as positive electrode active material E1.
[0106] <Positive electrode active materials H1, 2>
[0107] In the preparation of the positive electrode active material, the composition of the mixed hydroxide is changed to Ni 0.75 Mn 0.25 (OH)2, and except that the maximum reaching temperature was changed as shown in Tables 2 and 4, positive electrode active materials H1 and 2 were obtained in the same manner as positive electrode active material E1.
[0108] [Production of test unit]
[0109] Follow these steps to make Figure 2 The test unit shown. First, the positive electrode active material, acetylene black (conductive material), and polyvinylidene fluoride (binder) were mixed at a weight ratio of 80:10:10 and slurried using N-methyl-2-pyrrolidone. Next, the slurry was applied to an aluminum foil collector as a positive electrode collector and vacuum dried at 110°C to prepare a working electrode 30 (positive electrode).
[0110] In dry air with a dew point of -50°C or less, the electrode group with a separator 34 sandwiched between the working electrode 30, the counter electrode 31 (negative electrode) and the reference electrode 32, which are installed with an electrode connector 38, is housed in an outer casing 35, and then an electrolyte 36 is injected into the outer casing 35, and the outer casing 35 is sealed to prepare a test unit as a non-aqueous electrolyte secondary battery. Thus, test units A1 to H4 corresponding to the positive electrode active materials A1 to H4 are obtained. The details of each component are as follows.
[0111] Counter electrode: Lithium metal
[0112] Reference electrode: Lithium metal
[0113] Diaphragm: Polyethylene diaphragm
[0114] Non-aqueous electrolyte: LiPF6 as an electrolyte salt was dissolved at a concentration of 1.0 mol / l in a non-aqueous solvent obtained by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 3:7.
[0115] [Evaluation of charge capacity, discharge capacity and charge / discharge efficiency 1]
[0116] At an ambient temperature of 25°C, the test cell was charged to 4.5V (based on lithium) at a constant current of 0.2C, and then charged to 0.02C at a constant voltage of 4.5V. Then, it was discharged to 2.5V at a constant current of 0.1C. The charge capacity and discharge capacity at this time were measured, and the charge and discharge efficiency was calculated by dividing the discharge capacity by the charge capacity.
[0117] [Durability Evaluation 1]
[0118] At an ambient temperature of 25°C, the test unit was charged to 4.5V at a constant current of 0.2C, and then charged to 0.02C at a constant voltage of 4.5V. Then, it was discharged to 2.5V at a constant current of 0.1C. This charge and discharge was regarded as one cycle, and the measurement was performed under the above conditions in 11 cycles, 21 cycles, and 31 cycles. In the other cycles, the charge and discharge were performed in the same manner as above except that the constant current during discharge was set to 0.2C. The capacity retention rate was calculated by the following formula.
[0119] Capacity retention rate = (discharge capacity at the 31st cycle / discharge capacity at the 1st cycle) × 100
[0120] The evaluation results of the examples and comparative examples are shown in Tables 1 and 2. Table 1 shows the results of test cells A1 to D2, and Table 2 shows the results of test cells E1 to H2. The results of the single particle test unit are shown as examples, and the results of the test units other than the above are shown as comparative examples. For example, the results of the test unit F1 are shown as Example F1-1.
[0121] Table 1
[0122]
[0123] Table 2
[0124]
[0125] [Evaluation of charge capacity, discharge capacity and charge / discharge efficiency 2]
[0126] At an ambient temperature of 25°C, the test cell was charged to 4.7 V (based on lithium) at a constant current of 0.2C, and then charged to 0.02C at a constant voltage of 4.7V. Then, it was discharged to 2.5 V at a constant current of 0.1C. The charge capacity and discharge capacity at this time were measured, and the charge and discharge efficiency was calculated by dividing the discharge capacity by the charge capacity.
[0127] [Durability Evaluation 2]
[0128] At an ambient temperature of 25°C, the test unit was charged to 4.7V at a constant current of 0.2C, and then charged to 0.02C at a constant voltage of 4.7V. Then, it was discharged to 2.5V at a constant current of 0.1C. This charge and discharge was regarded as one cycle, and the measurement was performed under the above conditions in 11 cycles, 21 cycles, and 31 cycles. In the other cycles, the charge and discharge were performed in the same manner as above except that the constant current during discharge was set to 0.2C. The capacity retention rate was calculated by the following formula.
[0129] Capacity retention rate = (discharge capacity at the 31st cycle / discharge capacity at the 1st cycle) × 100
[0130] Tables 3 and 4 show the evaluation results of the examples and comparative examples. Table 3 shows the results of test units A1 to D3, and Table 4 shows the results of test units E1 to H2. The results of the single particle test cell are shown as examples, and the results of the test cells other than the above are shown as comparative examples. For example, the results of the test cell E1 are shown as Example E1-2.
[0131] Table 3
[0132]
[0133] Table 4
[0134]
[0135] In Tables 1 and 2, the test unit of the embodiment can take into account both the charging capacity and the capacity retention rate. On the other hand, in Tables 1 and 2, the charging capacity and the capacity retention rate of the test unit of the comparative example are worse than those of the embodiment. It can be seen that by making the single particle have a specified average particle size and crystallite size, high capacity and high durability can be taken into account. In addition, as shown in Tables 3 and 4, the single particle itself can also improve the battery characteristics, but by protecting the positive electrode surface with a boron compound, it also has the effect of improving the battery capacity, charge and discharge efficiency and capacity retention rate, and inhibiting the generation of gas.
[0136] The present disclosure is further illustrated by the following embodiments.
[0137] Technical composition 1:
[0138] A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide contains 70 mol % or more of Ni and Mn relative to the total molar amount of metal elements other than Li, the lithium transition metal composite oxide is composed of single particles, the average particle size of the single particles is 0.65 μm to 4 μm, and the crystallite size of the single particles is
[0139] Technical composition 2:
[0140] According to the positive electrode active material for a non-aqueous electrolyte secondary battery described in the technical configuration 1, when the BET specific surface area of the lithium transition metal composite oxide is set to A (m 2 / g), and the average particle size of the lithium transition metal composite oxide is set to B (μm), the product AB of A and B satisfies 1.5≤AB≤6.
[0141] Technical composition 3:
[0142] According to the positive electrode active material for a non-aqueous electrolyte secondary battery as described in the technical configuration 1 or 2, a surface modification layer containing a boron compound is formed on the surface of the single particle.
[0143] Technical composition 4:
[0144] According to the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of technical configurations 1 to 3, the lithium transition metal composite oxide further contains at least one metal element selected from the group consisting of Ca, Sr, W, S and P.
[0145] Technical composition 5:
[0146] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of the technical configurations 1 to 4 includes, in addition to the single particles, secondary particles formed by agglomerating the single particles.
[0147] Technical composition 6:
[0148] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of configurations 1 to 5 includes 10 mass % or more of the single particles based on the total amount of the positive electrode active material for a non-aqueous electrolyte secondary battery.
[0149] Technical composition 7:
[0150] A non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode active material for a non-aqueous electrolyte secondary battery as described in any one of technical configurations 1 to 6.
[0151] Description of Reference Numerals
[0152] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 diaphragm, 14 electrode body, 15 outer body, 16 sealing body, 17, 18 insulating plate, 19 positive electrode lead, 20 negative electrode lead, 21 slot, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cover, 26a opening, 27 gasket, 30 working electrode (positive electrode), 31 counter electrode (negative electrode), 32 reference electrode, 34 diaphragm, 35 outer body, 36 electrolyte, 38 electrode connector
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide, The lithium transition metal composite oxide contains 70 mol % or more of Ni and Mn relative to the total molar amount of metal elements other than Li, The lithium transition metal composite oxide is composed of single particles. The average particle size of the single particle is 0.65 μm to 4 μm. The crystallite size of the single particle is 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, The BET specific surface area of the lithium transition metal composite oxide is set to A and the unit is m 2 / g, and the average particle size of the lithium transition metal composite oxide is set to B and the unit is μm, the product AB of A and B satisfies 1.5≤AB≤6.
3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, A surface modification layer including a boron compound is formed on the surface of the single particle.
4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, The lithium transition metal composite oxide further includes at least one metal element selected from the group consisting of Ca, Sr, W, S and P.
5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, In addition to the single particles, secondary particles formed by agglomeration of the single particles are included.
6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, The single particles are contained in an amount of 10% by mass or more based on the total amount of the positive electrode active material for a non-aqueous electrolyte secondary battery.
7. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 6.
Citation Information
Patent Citations
Positive electrode active material for secondary battery and secondary battery containing the same
JP2018532236A